The Contribution of Board Games to Pre-Kindergarten Students' Oral Production - Leslie Werlinger B.; Maria-Jesus Inostroza A. (Asociación Colombiana de Profesores de Ingles, 2024)
During the last decades, global interest in learning English as a foreign language has increased, encouraging countries to include it in school education. This trend was followed by the Chilean Ministry of Education, which suggests teaching English based on a communicative approach starting in early childhood education. To foster students' learning, it is imperative to acknowledge that children learn differently than older learners and that English as a foreign language teachers should be able to identify their needs and implement age-appropriate strategies. This article reports the action research findings that explore the contribution of board games, memory, and bingo on pre-kindergarten students' oral expression when participating in English lessons. A group of 19 children aged four from a private school in Concepción, Chile, took part in this study by playing online and board bingo, and memory games. Data were gathered by qualitative methods, such as an observation checklist, a semi-structured interview applied to the co-teacher, and group interviews carried out with students at the end of the intervention. The group and semi-structured interview data were analyzed through the thematic data analysis technique, along with frequency data analysis used to process the observational checklists. The results show that students increased their English oral production when games were implemented in their lessons.